PERTAMBAHAN ESTIMASI KERUGIAN EKONOMI AKIBAT BANJIR DENGAN PENGARUH PENURUNAN TANAH DI JAKARTA - Yuhanafia, Nurul; Andreas, Heri (Jurnal Pendidikan Geografi Gea, 2017)
The land subsidences contributed to the widespread inundation of floods that occured in Jakarta. The purpose of this study is to calculate the increase in estimated economic losses due to floods that are affected by land subsidence. The main data used in this research is a Jakarta’s flood map. Calculation of loss estimation is done by combining flood map with land use map, and then adjusted to economic exposure value. This calculation is made with the assumption that there is no dynamics changes in the study area except the topography. The result of the calculation study shows that between 2007 to 2027 predicted that there will be an increase in economic loss of 15 T, from 21 T to become 36 T economic losses in 2027. It is necessary to take precautionary measures to reduce the occurrence of land subsidence in order to reduce the amount of economic losses due to the flood disaster.